Analyzing The Effectiveness of English Pop Songs As A Media to Improve Students’ Listening Comprehension - Angkouw, Thesalonika Natasya; Mogea, Tini; Rorimpandey, Rinny S (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study aims to assess the effectiveness of English pop songs in enhancing students' listening comprehension. A quantitative method was applied, utilizing a single-group pre-test and post-test design. The study included 20 ninth-grade students from SMP Negeri 2 Tondano as participants. Pre-test and post-test assessments were used to gather data. The findings indicated that incorporating songs can significantly enhance students' English listening comprehension, as demonstrated by the difference in average scores between the pre-test (56.00) and post-test (82.25). Songs were shown to improve vocabulary recognition, contextual understanding, and motivation to learn foreign languages, along with other listening skills. However, the effectiveness of music in language learning is influenced by several factors, such as the alignment of songs with learning objectives, students' proficiency levels, and the teaching approach used by instructors.